2017
DOI: 10.1051/e3sconf/20172401004
|View full text |Cite
|
Sign up to set email alerts
|

The influence of regional geological settings on the seismic hazard level in copper mines in the Legnica-Głogów Copper Belt Area (Poland)

Abstract: Abstract. The current level of rockburst hazard in copper mines of the (LGOM) Legnica-Głogów Copper Belt Area is mostly the consequence of mining-induced seismicity, whilst the majority of rockbursting events registered to date were caused by high-energy tremors. The analysis of seismic readings in recent years reveals that the highest seismic activity among the copper mines in the LGOM is registered in the mine Rudna. This study investigates the seismic activity in the rock strata in the Rudna mine fields ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 2 publications
(2 reference statements)
0
9
0
Order By: Relevance
“…A deep series of Tertiary sediments represent the Rotliegend and Zechstein strata. Sediments from the Neogene and Paleogene periods formed the youngest rock strata [61]. There are numerous fault zones in the study area (Figure 1B).…”
Section: Study Area and Input Datamentioning
confidence: 97%
See 1 more Smart Citation
“…A deep series of Tertiary sediments represent the Rotliegend and Zechstein strata. Sediments from the Neogene and Paleogene periods formed the youngest rock strata [61]. There are numerous fault zones in the study area (Figure 1B).…”
Section: Study Area and Input Datamentioning
confidence: 97%
“…These zones run northwestern to the southeast. The main faults range in inclination from 30 • to 90 • [61][62][63].…”
Section: Study Area and Input Datamentioning
confidence: 99%
“…The mining-induced seismicity and related rock burst hazard may be the function of several parameters: in LGCD, the principal factors influencing the seismic hazard level (measured by the number of registered seismic events and the total seismic energy released) are the regional geological setting, i.e., the effective mining thickness and the thickness of burst-prone roof rock strata, and the possible variation of tectonic stress intensity [36]. Limestones and anhydrites that lie above the ore store elastic strain energy that can be released through fracturing and rock bursts [19].…”
Section: Discussionmentioning
confidence: 99%
“…The roof of the LGCD mines consists of sub-horizontal limestone or dolomite strata 200 m thick, while anhydrite and gypsum layers, parallel to the bedding, lie above (Figure 2b). The ore is located above the basement rocks at the intersection with two NW-SE and NNE-SSW striking fault systems that control the regional distribution of the metal and the content of mineralization and its geometry [34]; the ore is tectonically disturbed by a dense grid of fractures and faults [35,36]. The dominant fault system in the mining area coincides with the fault zone of Rudna and Lubin (Figure 2a).…”
Section: Geological Settingmentioning
confidence: 99%
“…In the course of removal of rock the pillars degrade enabling gradual roof subsidence [1]. With the increasing depth of exploitation it was observed that increasing stress create more and more difficulties during the mining process [2]. Currently, the most significant hazard is associated with seismic activity resulting from disturbance of equilibrium state of primary stresses in the rock mass.…”
Section: Introductionmentioning
confidence: 99%